Analisa Diabetic Self Care Menggunakan Summary of Diabetes Self Care Activities (SDSCA) Pada Penderita Diabetes Melitus - Srywahyuni, Ade; Amelia, Dona; Zulita, Ovilia (Universitas Fort De Kock Bukittinggi, 2021)
Background: IDF reports that the number of people with Diabetes in 2019 was 463 million. This number will increase to 700 million in 2045. In, 2018 Riskesdas said that there was an increase in diabetes cases in Indonesia based on the results of blood glucose examinations from 6.9% in 2013 to 8.5% in 2018. The increase can be caused by the inability of the patient to carry out self-care optimally. This self-care ability can be assessed through the SDSCA instrument. The purpose of this study was to analyze self-care for people with diabetes in Bukittinggi. Methods: Study was designed as descriptive analytic with survey. Data were collected using a Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. Samples were taken by consecutive sampling for 155 respondents. Data were analysed by SPSS. Results: The results of this study indicate that self-care of people with diabetes are poor (16.1%), Averrage (66.5%), and good (17.4%). Conclusion: Primary health care is suggested to improve the health promotion programs, especially in terms of self-care for diabetes.